Pictorialism in the fictional miniatures of Albert Paris Gütersloh - Laue, Ingrid E. (Lang, 1996)
Pictorialism in the Fictional Miniatures of Albert Paris Gutersloh represents a first attempt in scholarly literature at highlighting the writer and painter Albert Paris Gutersloh's artistic duality by focusing on his
Keywords: Gutersloh; Albert Paris <1887-1973> - Critique et interprétation; Gütersloh; Albert Paris <1887-1973>; Gütersloh; Albert Paris; Art et littérature; Art and literature; Authors as artists; Malerei; Das Malerische; Kurzepik